Creep-rupture behavior of AISI 347 austenitic stainless steel foils at different temperature and stress levels - Osman, Ali Hassan (2011)
inbox unpub unspecified FKM 2011-00 completed 135 Universiti Teknologi Malaysia, Faculty of Mechanical Engineering Faculty of Mechanical Engineering phd thesis